Antimicrobial activity of nanostructured composites produced in Al/Zn nanoparticle oxidation in aqueous-alcoholic solutions; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Lozhkomoev A. S. Aleksandr Sergeevich; Glazkova E. A. Elena Alekseevna; Svarovskaya N. V. Natalia Valentinovna; Bakina O. V. Olga Vladimirovna; Khorobraya E. G. Elena; Timofeev S. S. Sergey; Domashenko V. V. Vladimir; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen